Antioxidative Effects of Nanocurcumin and Curcumin Against Aluminum Phosphide-induced Serum Oxidative Stress - Somayyeh Mohammadi Pasand (Hamadan University of Medical Sciences, 2020)
Objectives: Aluminum phosphide (AIP) is the commonly used pesticide in agriculture, which induces oxidative stress in almost all major body systems and organs. The aim of this study was to evaluate the efficacy of nanocurcumin and curcumin on serum oxidative stress level in subacute toxicity with AIP.